Potential drivers of spatial distribution of the ghost orchid, Dendrophylax lindenii, in a South Florida cypress strand: a preliminary study - Pieterson, Corrie (Universidad de Costa Rica, 2023)
This study examined a population of ghost orchids (Dendrophylax lindenii) in Fakahatchee Strand Preserve State Park in Collier County, Florida, to determine if they exhibit host species preference, vertical stratification, substrate diameter stratification, or a distribution pattern similar to their host plants. Twenty-five ghost orchids were found on three host plant species: 20 (80%) were on pop ash (Fraxinus caroliniana), four (16%) on arthritis vine (Hippocratea volubilis), and one (4%) on pond apple (Annona glabra). Our analysis indicated a statistically significant occurrence of ghost orchids on pop ash relative to other woody plant species in the study area. Although most orchids were found below 3 m from the forest floor, this was not statistically significant when compared to orchids above 3 m. A weak trend (p=0.06) for increasing occurrence was observed in the next to largest (14.1 cm to 17.2 cm diameter at breast height) size class among the five size classes of pop ash in this study. The spatial analyses indicated that both the stems of pop ash and ghost orchids demonstrate non-random clumping on the landscape. In addition, the presence of an individual orchid increases the probability of multiple ghost orchids on a stem. These results further emphasize the importance of pop ash as a host species in Florida’s ghost orchid populations and add to the list of hosts (arthritis vine) in the literature. Continuing to study the vertical position of ghost orchids will be important as climate change has the potential to alter humidity patterns and the occurrence of both low temperature events and hurricanes. Improved understanding of host plant preference, microhabitat requirements, spatial distribution, and continued long-term monitoring of population dynamics are critical for the conservation of the ghost orchid.